Tick control in Tswana, Simmental and Brahman cattle by means of Neem seed extracts (Azadirachta indica) - Webb, E.C. (Edward Cottington) (University of Pretoria, 2013)
Dissertation (MSc Agric (Animal Science))--University of Pretoria, 2006.